Security mechanism in access control based on non-cooperative game - Yi-xuan ZHANG; Jing-sha HE; Bin ZHAO (Tongxin xuebao)
Access control technology is an important information security technology to protect the sensitive information and critical resources in computer system and network.But traditional access control methods could only respond to access requests of users passively and can’t meet the changing dynamic network environment.In order to improve the ability to respond to malicious attacks and threats in access control system,a security mechanism is designed,which is suitable for access control,based on non-cooperative game theory in the game.When the subject makes an access request to the object,there will be a non-cooperative game between them to get Nash equilibrium.Then the security mechanism will compare the probabilities in the Nash equilibrium to the setting thresholds to get the conclusion that whether to authorize the subject or not.Experiment proves the effectiveness of the security mechanisms.